Price Volatility of Agricultural Products: Evidence From Producer Fruits Price in Batu Municipality, Indonesia - Sujarwo, Sujarwo; Hanani, Nuhfil; Fahriyah; Hamidatul Khofifah (Jurnal Manajemen & Agribisnis, 2023)
This paper attempts to investigate the price volatility of fruits with higher economic values, which are avocado, apple, guava, banana, and jackfruit, and analyzes the long-term and short-term period relationship between production and prices of these fruits. The data used are the quarterly productions and prices of avocado, apple, guava, banana, and jackfruit on the producer level for 2012 to 2020 obtained from Agriculture office of Batu Municipality. The volatility evaluation was using the ARCH/GARCH. The long-term relationship was analyzed using the Johansen cointegration test, and the short-term relationship used the Error Corection Mechanism (ECM). The results of the volatility analysis confirmed that every fruit studied had a low volatility rate. In addition, the productions and prices of the commodities studied had been cointegrated in the long-run; however only avocado, guava, and apple have a short-run relationship. The government is suggested to provide price and production information systems to ensure farmers' market access. Keywords: price volatility, fruits, ARCH/GARCH, cointegration, ECM